Artistic response to ecological problems in contemporary English-language ecopoetry - Zimina, Evgeniia V. (Вестник Томского государственного университета. Филология)
The paper summarizes the results of analysing contemporary British and American ecological poetry. The research aims to compare the approaches to composing British and American poetic texts focused on ecology. The results proved our hypothesis only in part. The new increasing number of ecological poems does not mean the shift towards ecoactivism. American poets tend to be more ecoactive, whereas British poets take an ecocritical stance. The major theme of the British poems under study is the lament of the gone English landscapes while American poems call for action. At the same time there is a visible growth in the number of English-language poems written by poets from countries that do not have a long tradition of environment protection.